Analisis Kapasitas Mesin Pencacah Limbah Plastik dan Tekstil Menggunakan Unit Penghancur (Shredder) - Rivan Muhfidin; Sely Novita Sari; Rizqi Prastowo (Universitas Islam Raden Rahmat, Malang, 2024)
Plastic garbage is a pressing ecological concern, with worldwide production reaching millions of tons annually, causing detrimental effects on both land and water. Recycling plastic garbage is an optimal solution. The objective of this study is to develop a plastic and fabric chopping machine that operates like a shredder. Experimental techniques will be employed to alter the current shredding machine, making it more streamlined and tailored to the requirements of the Ringas Trengginas Waste House. The test materials consist of PET, HDPE, and fabric waste. Data was gathered via observation and literature review, and then analyzed using machine manufacturing planning and waste disposal outcomes. This machine has the ability to shred 100 grams of plastic that is 0.3 mm thick in just 27 seconds, resulting in a shredding rate of 13.3 kg per hour. Similarly, it can shred plastic that is 0.5 mm thick in 30 seconds, resulting in a shredding rate of 12 kilogram per hour. Additionally, it can shred fabric that is 0.2 mm thick in 45 seconds, resulting in a shredding rate of 8 kg per hour. The mean engine capacity is 10.13 kg/hour.